2014
DOI: 10.1165/rcmb.2013-0195oc
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-326 Regulates Profibrotic Functions of Transforming Growth Factor-β in Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a fatal disorder resulting from the progressive remodeling of lungs, with no known effective treatment. Although transforming growth factor (TGF)-b has a wellestablished role in lung fibrosis, clinical experience with neutralizing antibodies to TGF-b has been disappointing, and strategies to directly suppress TGF-b1 secretion are needed. In this study we used a combination of in silico, in vitro, and in vivo approaches to identify microRNAs involved in TGF-b1 regulation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
123
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(130 citation statements)
references
References 35 publications
4
123
2
1
Order By: Relevance
“…There have been many successful efforts to harness miRs in treating human diseases, such as infectious and metabolic maladies (41,42). The roles of miRs in respiratory diseases, including pulmonary fibrosis, have also attracted a great deal of interest in recent years (23,25,26,30,(43)(44)(45). By targeting pro-or antifibrotic mediators, miRs can act as either negative or positive players in the pathogenesis of this disorder.…”
Section: Lentiviral Delivery Of Mir-27a-3p Attenuates Bleomycin-inducmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many successful efforts to harness miRs in treating human diseases, such as infectious and metabolic maladies (41,42). The roles of miRs in respiratory diseases, including pulmonary fibrosis, have also attracted a great deal of interest in recent years (23,25,26,30,(43)(44)(45). By targeting pro-or antifibrotic mediators, miRs can act as either negative or positive players in the pathogenesis of this disorder.…”
Section: Lentiviral Delivery Of Mir-27a-3p Attenuates Bleomycin-inducmentioning
confidence: 99%
“…There is a growing list of miRs that has been shown to regulate the pathogenesis of pulmonary fibrosis (25,26,30,(43)(44)(45). For example, miR-26a and miR-21 regulates TGF-b1 activity through targeting Smad4 and Smad7, respectively, in lung fibroblasts (25,44).…”
Section: Lentiviral Delivery Of Mir-27a-3p Attenuates Bleomycin-inducmentioning
confidence: 99%
“…The first report revealing the potential role of miRNAs in IPF demonstrated impressively by array analysis that 10% of the miRNAs were significantly different between IPF and control samples [121]. A series of elegant studies followed evaluating the miRNAs expression levels in IPF, such as the downregulation of members of Let-7, miR-29, miR-30, miR-31, miR-200, miR-326 and the miR-17-92 cluster, and the upregulation of miR-155 and miR-21 [121][122][123][124][125][126][127].…”
Section: Biomarkers In Ipf and Osamentioning
confidence: 99%
“…Approximately 10% of miRNAs expressed in the lungs of IPF patients show significant deregulation. 17 It has been found that miRNA-326, 18 let-7d, miRNA-29, miRNA-18a, 17 miRNA-26a, [18][19][20] and miRNA-200 21 are downregulated and miRNA-21, 22 miRNA-199a, 23 and miRNA-145 24 are upregulated in lungs of IPF patients. Alterations in these miRNAs have also been demonstrated in lung fibroblasts or alveolar epithelial cells from IPF patients and pulmonary fibrosis animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in these miRNAs have also been demonstrated in lung fibroblasts or alveolar epithelial cells from IPF patients and pulmonary fibrosis animal models. 17,18,[21][22][23][24] However, changes in miRNAs in PMCs and their roles in PMC EMT and sub-pleural fibrosis have not been described. In the present study, we used cultured PMCs and a mouse pulmonary fibrosis animal model to explore the role of miRNA in PMC EMT and sub-pleural pulmonary fibrosis.…”
Section: Introductionmentioning
confidence: 99%